Bloodlands. Series 2 [videorecording (DVD)] - Brandon, Chris, 1981- (Acorn, 2023)
An accountant's murder pulls DCI Tom Brannick into a hunt for a fortune that he's been hiding since his days as "Goliath." He is allied with the victim's widow, but as Tom tries to conceal their trail, he comes closer to being unmasked.